Preparation and thermal decomposition of solid state cinnamates of alkali earth metals, except beryllium and radium - Chiaretto, Ana Glauce Zaina; Carvalho Filho, Marco Aurélio da Silva; Fernandes, Nedja Suely; Ionashiro, Massao (Eclética Química, 1998)
Solid state compounds of general formula ML2.nH2O [where M is Mg, Ca, Sr or Ba; L is cinnamate (C6H5-CH=CH-COO-) and n = 2, 4, 0.8, 3 respectively] have been synthetized. Thermogravimetry (TG), derivative thermogravimetry (DTG), differential scanning calorimetry (DSC) and X-ray diffraction powder patterns have been used to characterize and to study the thermal stability and thermal decomposition of these compounds.